If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27 = 3(2x + -7) Reorder the terms: 27 = 3(-7 + 2x) 27 = (-7 * 3 + 2x * 3) 27 = (-21 + 6x) Solving 27 = -21 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 27 + -6x = -21 + 6x + -6x Combine like terms: 6x + -6x = 0 27 + -6x = -21 + 0 27 + -6x = -21 Add '-27' to each side of the equation. 27 + -27 + -6x = -21 + -27 Combine like terms: 27 + -27 = 0 0 + -6x = -21 + -27 -6x = -21 + -27 Combine like terms: -21 + -27 = -48 -6x = -48 Divide each side by '-6'. x = 8 Simplifying x = 8
| -11x-400-.03x=840 | | 27=15+9 | | 3x-9=5x+2 | | -1.08=0.9v | | 2x+2y=2x+9 | | 4x^2-8x+4y^2+12y-131=0 | | 6s+2=-10 | | K-7+6= | | 12n-17n+6=32 | | v^2-4vx-12x^2=0 | | 3x(2)=12+5x | | 96=16+2x | | 9(t-6)+3=6(2t+3)-9 | | (17b-5)-4(4b+4)=-6 | | (X^2+4)=25 | | 2a+8a=8 | | (2x-4)-(5x+3)= | | 4c-43=7c-193 | | 44=4(x-5) | | -43=2+9x | | 3(y-7)=2(4+y) | | 4m=m+21 | | 20x^2-25+5= | | -2=4r-s | | 4(j-3)=23-3j | | 2x+5(x-18)=-174 | | 90=-8y+50 | | -5a+3=1 | | 2m=5m+60 | | -3(v+9)=-8v+8 | | 2-5x=3x-86 | | -5x-2(-6x+10)=-97 |